Prevention, Identification, and Management of Stunting through Health Education and Entrepreneurial Capacity Building in Argomulyo Village, Sleman, Yogyakarta - Torana Kurniawan; Yana Supriatna; Sri Dwidanarti; Lina Choridah; Anita Ekowati; Wigati Dhamiyati; Bambang Supriyadi; Mohammad Rizki Pratama; Abdi Alhaq (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
Stunting is one of the world’s most serious public health issues, with significant morbidity rates, especially in Indonesia. Low public awareness of stunting and low family income are two major causes discovered especially in Special District of Yogyakarta. This community service project was undertaken to address this issue. Following the completion of the situation analysis and problem identification, a community-based problem-solving strategy in the form of health and entrepreneurship education was developed. Three medical experts provided prenatal health education to pregnant women, followed by an ultrasound screening to detect any early anomalies related to stunting. For other members of the community, experienced entrepreneurs give entrepreneurial education, which was supported by workshops for them to immediately practice the material that had been presented. It was intended that the community’s excitement would raise health awareness about stunting and the level of the local economy, allowing the stunting problem in this region to be ameliorated. It was found that the provision of health education programs had succeeded in increasing the level of community knowledge regarding stunting. Ultrasound examination found that all pregnant women in the area had normal pregnancies and fetal conditions. Community-based interventions through health education and increasing economic welfare based on tourism villages can be used to prevent stunting.